Surgery for complicated pulmonary tuberculosis - Ganie, Farooq Ahmad; Wani, Nasir Uddin; Gani, Masarat-ul; Hakeem, Zubair Ashraf; Bhat, Mudasir Hamid; Naqash, Iqra Nazir (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Abstract not available